Understanding Leadership Principles and Team Dynamics in Nonprofit Settings: A Study of Short and Long-Term Missionary Teams - Midgett, Samantha (East Carolina University, 2022)
Have you ever pondered how to form the most effective leadership team for missionary work? Missionary work is extremely important to the Christian Church and building leaders within the church community. Without them, others wouldn’t get to hear the gospel. This research could benefit someone who wants to pursue a career in ministry. One field of ministry and possible career choice someone could pursue is to become a missionary. Performing this research means learning more about how to be effective in a career choice such as a missionary. In addition to that, it could benefit someone who is a business major. In this major a person learns a lot about teamwork and leadership and is exposed to working in some highly effective teams, and also some that are not so effective. This research will discover how missionary teams (both short and long-term) can be most effective in accomplishing the task at hand. It will also show what leadership looks like on a mission field and how to bring that leadership, along with a short-term team, to be most helpful to the missionaries already on the field. The findings from this research will help those in the field of ministry to become the best missionary they can be, whether they become a long-term missionary on the field, or occasionally go to help on short-term trips.
Keywords: Missions; long-term missions; short-term missions; nonprofit; Christian; team dynamics; leadership; leadership development